2022
DOI: 10.3390/foods11142022
|View full text |Cite
|
Sign up to set email alerts
|

Application of Pulsed Electric Fields to Pilot and Industrial Scale Virgin Olive Oil Extraction: Impact on Organoleptic and Functional Quality

Abstract: The quality of virgin olive oil (VOO) is largely determined by the technology used in the industrial process of extracting the oil. Technological innovations within this field aim to strike a proper balance between oil yield and the optimal chemical composition of VOO. The application of pulsed electric fields (PEF) that cause the electroporation of the plant cell membranes favors a more efficient breakage of the olive fruit tissue, which in turn could facilitate the extraction of the oil and some of its key m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
(47 reference statements)
3
13
0
Order By: Relevance
“…This seems to promote the release and transfer of polar molecules such as 3,4- DHPEA-EDA into the oil phase, which is known to slow down the negative oxidative phenomena in EVOO [ 34 ] and improve sensory and health properties [ 33 ]. The higher amount of oleuropein derivatives in EVOOs obtained after PEF treatment in olive pastes observed in this work is consistent with previous studies [ 19 , 23 , 29 , 38 ]. The ability of PEF technology to improve the solubility of oleuropein derivatives has already been described by Veneziani et al [ 29 ], who observed an increase in these phenolic compounds responsible for health-promoting benefits depending on the different olive varieties and their maturity index.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This seems to promote the release and transfer of polar molecules such as 3,4- DHPEA-EDA into the oil phase, which is known to slow down the negative oxidative phenomena in EVOO [ 34 ] and improve sensory and health properties [ 33 ]. The higher amount of oleuropein derivatives in EVOOs obtained after PEF treatment in olive pastes observed in this work is consistent with previous studies [ 19 , 23 , 29 , 38 ]. The ability of PEF technology to improve the solubility of oleuropein derivatives has already been described by Veneziani et al [ 29 ], who observed an increase in these phenolic compounds responsible for health-promoting benefits depending on the different olive varieties and their maturity index.…”
Section: Resultssupporting
confidence: 93%
“…However, previous studies suggest that the variability of the content of this compound in EVOO is not influenced by processing conditions, while its actual content in oils depends on genetic and agronomic factors [ 39 ]. Our results are supported by a recent work [ 38 ] that investigated the differential effects of PEF treatment on secoiridoid derivatives as well as on tocopherol content. Our results differ from those of Abenoza et al [ 19 ] and Puértolas et al [ 20 ], who reported a higher increase in α-tocopherol content in EVOO from PEF treatment compared to EVOO from the traditional mechanical extraction process.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…However, the application of this claim is restricted to those oils that contain at least 250 ppm of hydroxytyrosol and its derivatives [ 5 ]. This EFSA health claim has promoted the development of different lines of research to obtain oils enriched in HTy derivatives, such as a better understanding of the metabolism of phenolic compounds in the olive, through the identification of key enzymes/genes, the development of new extraction technologies that favor the accumulation of phenols [ 6 ] or the search for molecular markers that could help olive breeders in the identification of new olive genotypes with improved phenolic profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several novel and emerging technologies have been developed and applied to satisfy the growing consumer demand for VOO with higher quality and healthrelated composition, such as microwaves [27,28], pulsed electric fields (PEF) [29][30][31][32][33][34][35], and ultrasound treatments [27,[36][37][38][39][40][41][42][43][44][45][46][47]. Moreover, these technologies have been studied for their capability to enhance VOO chemical-sensory quality, as well as its health-related composition.…”
Section: Introductionmentioning
confidence: 99%